ТЕТРАЭДР УШЫН БИССЕКТРИСА ТҮСИНИГИ ҲӘМ ОНЫҢ ҚӘСИЙЕТЛЕРИ - Танирбергенов, С.А. (ILIM hám JÁMIYET, 2018)
In the article the author studies the bisectorial plane and bisectrix of a tetrahedron, which is the space analogue of a triangle. It has been proved that the center of inside circle is on the crossed bisectrixes of a tetrahedron.